Assessment of Minimum Inhibitory Concentrations of Telavancin by Revised Broth Microdilution Method in Phase 3 Hospital-Acquired Pneumonia/Ventilator-Associated Pneumonia Clinical Isolates. Issue 4 (December 2016) - Smart, Jennifer; Corey, Gordon; Stryjewski, Martin; Wang, Whedy; Barriere, Steven
Abstract Introduction The broth microdilution method (BMD) for testing telavancin minimum inhibitory concentrations (MICs) was revised (rBMD) in 2014 to improve the accuracy, precision, and reproducibility of the testing method. The aim of this study was to determine the effect of the revised method on telavancin MIC values forStaphylococcus aureus (S. aureus ) clinical isolates obtained from hospital-acquired pneumonia (HAP) patients. Methods Isolates from patients who participated in the phase 3 Assessment of Telavancin for Treatment of HAP Studies were retested using the rBMD method. Results Retesting of 647 isolates produced a range of telavancin MIC values from 0.015 µg/mL to 0.12 µg/mL with MIC50/90 values of 0.06/0.06 µg/mL for the total pool of samples. For methicillin-resistantS. aureus (MRSA), MIC50/90 values were 0.06/0.12 µg/mL. These values are up to 4-fold lower than MIC50/90 values obtained using the original method. These results were used in part to justify lowering the telavancin breakpoints. All tested isolates remained susceptible to telavancin at the revised susceptibility breakpoint of ≤0.12 µg/mL. Overall, the clinical cure rate for microbiologically evaluable telavancin-treated patients was 78% forS. aureus, 76% for patients with MRSA, and 79% for patients with isolates with reduced susceptibility to vancomycin (MIC ≥1 µg/mL). Conclusion Results from the rBMD method support the in vitro potency of telavancin againstS. aureus . Trial registration ATTAIN (NCT00107952 and NCT00124020). Funding Theravance Biopharma Antibiotics, Inc.